INTELLECTUAL CAPITAL TERHADAP NILAI PASAR DAN KINERJA KEUANGAN PERUSAHAAN DENGAN MENGGUNAKAN VALUE ADDED INTELLECTUAL COEFFICIENTS (VAIC) PERUSAHAAN REAL ESTATE DAN PROPERTY YANG LISTING DI BURSA EFEK INDONESIA - Elfiswandi, Elfiswandi (Jurnal Ekobistek, 2013)
This study aims to examine and analyze the influence of intellectual capital on market value and financial performance of the company by using Value Added Intellectual Coefficient (VAIC). The research was conducted in real estate and property companies listed on the Indonesia Stock Exchange (IDX). In this study the authors used secondary data. The data used is data 9 real estate companies and property were selected as sample of the years 2007-2011. The technique of collection data by using documentation method. The analysis of method used is the classic assumption test, simple regression analysis and hypothesis testing. From the results of the quantitative analysis indicate that intellectual capital (VAIC) a significant effect on the market value (PER) with a sig. smaller than alpha (0.022 <0.05). Intellectual capital (VAIC) a significant effect on financial performance (ROA) with the sig. smaller than alpha (0.000 <0.05) Finally, the authors suggest for the real estate and property companies to pay more attention and increase intangible assets such as intellectual capital. Intellectual capital in the form of human and structural capital of the company. Human resources and skills can be improved by conducting employee recruitment and training, and provide rewards for high performing employees. Structural capital can be increased by fixing the structure organization and the relationship with the customer. Keywords: Intellectual Capital, Market Value, Corporate Financial Performance.